Proof-of-Concept Application - Annual Report Year 2 - Oscar Ardaiz; Pablo Chacin; Isaac Chao; Juan Carlos Cruellas; Felix Freitag; Manuel Medina; Leandro Navarro; Miguel Valero; Liviu Joita; Omer F. Rana; Torsten Eymann (Universität Bayreuth, Lehrstuhl für Wirtschaftsinformatik, 2006)
This document first gives an introduction to Application Layer Networks and subsequently presents the catallactic resource allocation model and its integration into the middleware architecture of the developed prototype. Furthermore use cases for employed service models in such scenarios are presented as general application scenarios as well as two very detailed cases: Query services and Data Mining services. This work concludes by describing the middleware implementation and evaluation as well as future work in this area.
urn:nbn:de:bvb:703-opus-3658
Keywords: 330; Grid Computing